2018
DOI: 10.1371/journal.pone.0197470
|View full text |Cite
|
Sign up to set email alerts
|

The influence of spinal-pelvic parameters on the prevalence of endplate Modic changes in degenerative thoracolumbar/lumbar kyphosis patients

Abstract: BackgroundThe typical degeneration of the vertebral endplate shown in MRI imaging is Modic change. The aim of this study was to observe the distribution of the Modic changes of vertebral endplate in degenerative thoracolumbar/lumbar kyphosis (DTK/LK) patients and analyse the correlation between spinal-pelvic parameters and Modic changes.MethodsThe imaging data of 58 patients diagnosed with DTK/LK (coronal Cobb angle<10°with sagittal imbalance) in our hospital from March 2016 to May 2017 were reviewed retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Farshad-Amacker et al [21] performed a long-term follow-up study to look for the predictors for the development of lumbar degeneration in terms of LDD and MCs, but they did not find the relationships between LL, SS, and the development of MCs. However, another study [15] with the contradictory results reported that the endplates with MCs in degenerative thoracolumbar/lumbar kyphosis were negatively correlated with LL ( r = − 0.562, P = 0.012) and SS ( r = − 0.46, P = 0.048). Obviously, the different conclusions of the above studies were based on different research subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farshad-Amacker et al [21] performed a long-term follow-up study to look for the predictors for the development of lumbar degeneration in terms of LDD and MCs, but they did not find the relationships between LL, SS, and the development of MCs. However, another study [15] with the contradictory results reported that the endplates with MCs in degenerative thoracolumbar/lumbar kyphosis were negatively correlated with LL ( r = − 0.562, P = 0.012) and SS ( r = − 0.46, P = 0.048). Obviously, the different conclusions of the above studies were based on different research subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Because degenerative sagittal imbalance can alter the axial stress of spinal motion unit, then, long-term axial stress can undoubtedly lead to the lesions of endplate and intervertebral disc. Meanwhile, deformation of intervertebral disc and endplate can in turn aggravate the sagittal imbalance of lumbar spine [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although FCLs are observed in axSpA, they are also present in degenerative and other spinal disorders [23] which could contribute to the differences in specificity. Among all vertebral levels, the thoracic spine is the least affected by degeneration [24, 25], rendering a more accurate diagnostic tool for axSpA.…”
Section: Discussionmentioning
confidence: 99%
“…SS is used to evaluate the normal variation in the sagittal plane of the adult human lumbar spine and pelvis in the standing position [27]. A recent study reported by Xia et al [28] supports that the amount of MCs was significantly correlated with LL and SS. This is coincident with our study.…”
Section: Lumbar Sagittal Parametersmentioning
confidence: 90%
“…This is coincident with our study. The associations of LL and SS with risk of MCs may be due to decreased axial decompression ability of the spine and an increased shear force on the vertebral endplate [28]. This would increase the risk of endplate and cancellous bone damage when the spine is subjected to external forces in the perpendicular direction [29].…”
Section: Lumbar Sagittal Parametersmentioning
confidence: 99%